Comparison of abiotic ecosystem services in exceptional landscapes conditioned by relief in the Martins-Portalegre massif, Brazilian semi-arid region - Francisco Herminio Ramalho de Araújo; Marco Túlio Mendonça Diniz; Marcelo Alves de Souza (Discover Geoscience)
Abstract This work studied the provision of ecosystem services by geodiversity, i.e., abiotic ecosystem services, which are classified into four types: regulating, provision, cultural and support. Each service consists of various benefits. The aim was to identify and draw up a comparison between the ecosystem services provided by exceptional landscapes and their surroundings. An evaluation method based on the Millennium Ecosystem Assessment was proposed. In the study area, the exception in the landscape is the relief, which conditions the climate and all the abiotic ecosystem service provision in the area. In this area, the degree of relevance of the ecosystem service provision is greater than in the dominant landscape. This greater provision of services in the exception area is conditioned by the relief.